Effect of the unbalanced magnetic pull force and oil-film force on nonlinearity of a dual-rotor bearing system. (December 2022) - Ma, Chenyuan; Zhao, Daoli; Liao, Weili; Sun, Weipeng; Guo, Pengcheng; Xu, Yanhe
Turbogenerator sets, the indispensible rotating machinery in thermal power plants, can be simplified into a dual-rotor bearing system. In this case, its nonlinear phenomenon largely results from the unbalanced magnetic pull (UMP) and the nonlinear oil film forces, which, however, are not well understood. In this study, a mathematical model for a dual-rotor bearing system is established, the effects of the UMP and the oil-film forces on its nonlinear phenomenon are investigated creatively. Of which, the UMP force is initially calculated by the integration of the air-magnetic energy, and the short journal bearing assumption is employed to derive the oil-film force. The fitness of the developed model is validated through the stability experiments of a 660 MW turbogenerator set. Results indicate that in the idling condition, nonlinear phenomenon of the system can be described as the period-1 and quasi-periodic motions as the rotational speed rises. At low speeds, the amplitude of oil whirl appears. With the rising rotational speed, the oil whirl turns into oil whip in the second quasi-periodic. Interestingly, the electromagnetic force can greatly alleviate the system amplitude and enhance its stability considering the UMP force. The nonlinear effect of air-gap distance of the system under load conditions is also investigated. The system is still in the quasi-periodic state with the increasing air-gap distance at low/high speed. But the system is still unstable owing to oil whirl/whip and UMP force, causing the system experiences multiple states and becomes more stable at the intermediate speed.